Code-mixing aspect in tourism text - Wisudawanto, Rahmat (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
The diversity of ethnic groups in Indonesia contributes to the phenomenon of language use. In the context of tourism, the use of language must attract tourists to visit a tourism place or tourism agenda. The use of language in Indonesia tourism also needs to consider to multilingual communities as target tourists. Communication between tourism service providers and tourists can use various media. The use of electronic and print media allows tourism practitioners to communicate effectively. The Solo Calendar of Events 2021 booklet published by the Surakarta government is an effort to be able to communicate with a wider community. This study aims to explain the use of variety language in tourism texts. This study focuses on explaining the phenomenon of the variety of language use in tourism texts. This study used a sociolinguistic approach and descriptive qualitative methods to describe the language used in tourism texts. The results of the study show that the variety of languages used in the tourism text of the Solo Calendar of Events 2021 is Indonesian, Javanese, and English languages. The presence of multilingual tourists results in the use of code mixing in the text. Factors that contribute to code mixing include branding, language attitude, and language power. Keywords: Language Variation, Tourism Text, Sociolinguistics, Communication, Code Mixing